An Examination of the Principle of Due Care in the Regional Government’s Policy on the Construction of the Kelingking Beach Lift - Elizabeth Prima Ratrisari; Jason Matthew; Jemimah Puteri Rajagukguk; Olivia Panjiani Napitu; Shintia Januarita; Veronica Enjelina Manalu (Universitas Ibn Khaldun, 2026)
Large-scale tourism infrastructure development in coastal areas often triggers conflicts between economic interests and ecological sustainability. This study examines the case of the construction of a glass elevator at Kelingking Beach, Nusa Penida, which was halted by the Bali Provincial Government due to various regulatory violations. The main focus of this research is to analyze the extent of the authority of local governments in controlling tourism development following the enactment of the Job Creation Law, as well as how the principles of sustainable tourism are integrated into regional policies. Using a normative legal research method, the findings indicate that the project violated five fundamental legal instruments, including spatial planning non-compliance, the absence of a Sea Space Utilization Approval, and the neglect of Bali’s cultural tourism standards. This analysis concludes that although business licensing procedures have been simplified through the Online Single Submission system, local governments still possess both attributive and delegative authority in supervisory and spatial control functions to ensure environmental carrying capacity sustainability and the protection of local wisdom.